PENGARUH MOTIVASI TERHADAP KINERJA PERAWAT DI RUANG RAWAT INAP DI RSU SEMBIRING DELITUA TAHUN 2019 - Sentosa Barus (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
The primary role is to manage the implementation of health care such as training programs, trainers and participate in program activities are responsible. In other words, health care workers assigned as managing existing activities. Lack of motivation and retraining or refresher training for employees of the health department and the lack of guidance led to a lack of ability of public health officials in performing their duties. This resulted in an inaccuracy in the execution of his duty personnel. Therefore, it needs to be researched